2011
DOI: 10.2478/v10102-011-0004-z
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of metabolic activity of phagocytes by antihistamines

Abstract: The purpose of the study was to investigate the effects of H1-antihistamines of the 1st generation (antazoline, bromadryl, brompheniramine, dithiaden, cyclizine, chlorcyclizine, chlorpheniramine, clemastine) and the 2nd generation (acrivastine, ketotifen, and loratadine) on the respiratory burst of phagocytes. Reactive oxygen species generation in neutrophils isolated from rat blood was measured using luminol-enhanced chemiluminescence. Changes in nitrite formation and iNOS protein expression by RAW 264.7 macr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
4
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 15 publications
0
3
4
2
Order By: Relevance
“…32 In the present study, cyclizine did not inhibit NO generation or iNOS expression in RAW264.7 cells. 32 Conversely, NO generation and iNOS expression were significantly induced by cyclizine at concentrations of 200, 300, and 500 μM. Therefore, cyclizine in macrophages may stimulate proinflammation through the overexpression of proinflammatory cytokines and mediators.…”
Section: Discussioncontrasting
confidence: 48%
“…32 In the present study, cyclizine did not inhibit NO generation or iNOS expression in RAW264.7 cells. 32 Conversely, NO generation and iNOS expression were significantly induced by cyclizine at concentrations of 200, 300, and 500 μM. Therefore, cyclizine in macrophages may stimulate proinflammation through the overexpression of proinflammatory cytokines and mediators.…”
Section: Discussioncontrasting
confidence: 48%
“…In parallel it has been demonstrated that 2-thioxanthine derivatives are suicide substrates of MPO, e.g., 2-isobutyl thioxanthine (IC 50 = 0.87 μM). Other compounds that affected MPO activity were H1-antihistaminic drugs and naphthalene derivatives, e.g., 6-methoxy1-ethyl-3,4-dihydro-naphthalene (IC 50 = 3 μM) . In any case, these studies have shown that there is additional need for alternative scaffolds to conceive more efficient inhibitors with activity in the nanomolar range …”
Section: Introductionmentioning
confidence: 98%
“…Histamine was shown to stimulate release of hydrogen peroxide by primary bronchial epithelial cells via H 1 receptor-dependent signaling [ 28 ]. Several H 1 -antihistamines diminished the production of ROS in neutrophils isolated from rat blood [ 29 ]. Moreover, it may be possible that levocetirizine inactivates ROS through direct scavenging activity or via activation of SOD, the only antioxidant enzyme that can scavenge superoxide [ 30 ].…”
Section: Discussionmentioning
confidence: 99%